Strengthening participation by young women sex workers in HIV programs: reflections on a study from Bangkok, Thailand - Conn C; Modderman K; Nayar S (Dove Medical Press, 2017)
Cath Conn, Kristel Modderman, Shoba Nayar School of Public Health and Psychosocial Studies, Auckland University of Technology, Auckland, New Zealand Background: Participation is an accepted means of increasing the effectiveness of public health programs, and as such, it is considered an important component of HIV interventions targeting at-risk youth. The situation of young women sex workers in Thailand is alarming on many fronts, including that of HIV risk. As a result, HIV programs in Thailand are the key interventions undertaken in relation to young women sex workers’ health. A small-scale study used semistructured interviews to explore the participation reports of five young women sex workers, as well as the related views of two community support workers, who lived and worked in Bangkok, Thailand.Discussion: This study is considered in the light of current research on – as well as new opportunities and challenges offered for – participation by vulnerable groups in the context of digital society. Thematic analysis of the interview data identified barriers to participation, including the illegality of sex work, fear, and lack of trust of the authorities, as well as widespread social stigma. Such barriers resulted in young women seeking anonymity. Yet, promisingly, young women positioned themselves as experts; they are involved in peer education and are supportive of greater involvement in HIV programs, such as further educational initiatives and collective actions.Conclusion: There is a need for a more empowerment-oriented participation practice positioning young women sex workers as expert educators and codecision makers within a model of participation that is also accountable, such as including young women as members of program boards. Beyond current norms, there are new opportunities emerging because of the increasing availability of smartphone/Internet technology. These can support activist and codesign participation by young women sex workers in HIV programs. However, any developments in participation must maximize opportunities carefully, taking into consideration the difficult social environment faced by young women sex workers as well as the need for strategies to address illegality and stigma. Keywords: community participation, prosumer, epublic health, peer educator, stigma